Thin film preparation method, photoelectric device and display device
By using a composite material of organic compounds and metal oxide inorganic nanomaterials enriched with metal ions in optoelectronic devices, semi-free radicals are generated through light treatment and combined with inorganic nanomaterials, the dissolution of inorganic nanomaterials by solution method is solved by the solution method. The problem has improved the anti-soluble and performance of optoelectronic devices.
Patent Information
- Application Number
- CN202310851876.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-14
AI Technical Summary
During the preparation of optoelectronic devices, the organic solvent used in the solution method is prone to dissolving and eroding the inorganic nanomaterials, resulting in damage to the functional layer structure and performance losses, affecting the performance and life of the optoelectronic devices.
Using composite materials, including organic compounds and doped metal oxide inorganic nanomaterials enriched by doped metal ions, the semi-free radicals are generated through light treatment and doped metal ions on the surface of the inorganic nanomaterial to reduce the solubility of the film in polar solvents. Improves resistance to solubility.
It improves the resistance to solubility and solution erosion resistance of functional films, extends the life of optoelectronic devices and improves their performance.
Smart Images

Figure CN119317308A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of optoelectronics, and in particular to a method for preparing a thin film, an optoelectronic device and a display device. Background Art
[0002] Optoelectronic devices such as quantum dot electroluminescent devices (QLED), organic electroluminescent devices (OLED), and perovskite solar cells are all multifunctional layer composite structures, generally including two electrodes and a functional layer arranged between the two electrodes, wherein the functional layer includes an electronic functional layer that can promote electron transport and injection, and the material of the electronic functional layer is usually inorganic nanomaterials such as ZnO and TiO2.
[0003] In the process of preparing optoelectronic devices, when the functional layer is prepared by the solution method, the organic solvent used in the solution method can easily dissolve and scour the inorganic nanomaterials, causing structural damage and performance damage to the functional layer, thereby affecting the performance and life of the optoelectronic device.
[0004] Therefore, how to improve the solubility resistance of the electronic functional layer has become a research direction for improving the performance of optoelectronic devices. Summary of the invention
[0005] In a first aspect, the present application provides a method for preparing a thin film, comprising:
[0006] A composite material is provided, the composite material comprising an organic compound and an inorganic nanomaterial, the inorganic nanomaterial comprising a metal oxide and a doped metal ion;
[0007] placing the composite material on a substrate and subjecting it to light treatment to obtain the film;
[0008] Wherein, the structure of the organic compound is shown in formula (I):
[0009]
[0010] Each R1 is independently selected from hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, unsubstituted or substituted with amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1-C20 chain hydrocarbon group, C1-C20 chain hydrocarbon oxy group, cycloalkyl group with 3 to 60 ring atoms, heterocycloalkyl group with 3 to 60 ring atoms, aryl group with 5 to 60 ring atoms, heteroaryl group with 5 to 60 ring atoms, aryloxy group with 5 to 60 ring atoms, heteroaryloxy group with 5 to 60 ring atoms, two adjacent R1s may form a ring or not, and n is selected from any integer from 0 to 4;
[0011] R2 is selected from one of -C(R3)3, -N(R4)2, and -OR5;
[0012] wherein R3 is independently selected from hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, a C1-C20 chain hydrocarbon group, a C1-C20 chain hydrocarbon oxy group, a cyclic hydrocarbon group having 3 to 60 ring atoms, a heterocyclic hydrocarbon group having 3 to 60 ring atoms, an aryl group having 5 to 60 ring atoms, a heteroaryl group having 5 to 60 ring atoms, an aryloxy group having 5 to 60 ring atoms, and a heteroaryloxy group having 5 to 60 ring atoms, which is unsubstituted or substituted with amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, or cyano;
[0013] R4 is independently selected from hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, thiol, cyano, a combination of one or more of unsubstituted or amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, thiol, cyano, C1-C10 alkoxycarbonyl, C1-C10 chain hydrocarbon group, C3-C10 cycloalkyl substituted C1-C20 chain hydrocarbon group, C1-C20 chain hydrocarbon group, cycloalkyl group with 3 to 60 ring atoms, heterocycloalkyl group with 3 to 60 ring atoms, aryl group with 5 to 60 ring atoms, heteroaryl group with 5 to 60 ring atoms, aryloxy group with 5 to 60 ring atoms, heteroaryloxy group with 5 to 60 ring atoms, and two adjacent R4s may form a ring or not;
[0014] R5 is independently selected from hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, a combination of one or more of C1-C20 chain hydrocarbon groups, C1-C20 chain hydrocarbonoxy groups, cyclic hydrocarbon groups having 3 to 60 ring atoms, heterocyclic hydrocarbon groups having 3 to 60 ring atoms, aryl groups having 5 to 60 ring atoms, heteroaryl groups having 5 to 60 ring atoms, aryloxy groups having 5 to 60 ring atoms, and heteroaryloxy groups having 5 to 60 ring atoms, which are unsubstituted or substituted with one or more of amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1-C20 alkyl, -(C=O)-R7, and R7 is selected from one or more of C1-C20 alkyl groups, aromatic ring groups having 6 to 40 ring atoms, and aromatic heterocyclic groups having 5 to 40 ring atoms.
[0015] In a second aspect, the present application provides a photoelectric device, comprising: a first electrode and a second electrode arranged opposite to each other; and a functional layer arranged between the first electrode and the second electrode, wherein the functional layer comprises a thin film produced by the above-mentioned thin film production method.
[0016] In a third aspect, the present application provides a display device, comprising the above-mentioned optoelectronic device
[0017] The method for preparing the film of the present application comprises providing a composite material, wherein the composite material comprises an organic compound and an inorganic nanomaterial, wherein the inorganic nanomaterial comprises a metal oxide and a doped metal ion; and placing the composite material on a substrate and performing a light treatment to obtain a film. When the method of the present application is used to prepare a functional film layer, the organic compound reacts under light treatment to generate a semi-radical R2, and the semi-radical R2 combines with the doped metal ion on the surface of the inorganic nanomaterial, thereby reducing the solubility of the film in polar solvents, improving the solubility resistance of the functional film, and thus improving the performance and life of the optoelectronic device. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 A schematic diagram of a process of an embodiment of a method for preparing a thin film provided in the present application;
[0020] Figure 2 A schematic diagram of the connection between a semi-free radical R2 and the surface of the inorganic nanomaterial in a method for preparing a thin film is provided for this application;
[0021] Figure 3 A schematic structural diagram of an embodiment of a photoelectric device provided in the present application;
[0022] Figure 4 A schematic structural diagram of another embodiment of a photoelectric device provided in the present application;
[0023] Reference numerals:
[0024] Optoelectronic device 100, first electrode 10, second electrode 20, light-emitting layer 32, electron functional layer 31, first electron transport layer 311, second electron transport layer 312, hole functional layer 33, hole transport layer 331, hole injection layer 332;
[0025] Optoelectronic device 200 , first electrode 210 , functional layer 230 , second electrode 220 , first hole functional layer 231 , first light-emitting layer 232 , first electron functional layer 233 , second hole functional layer 234 , second light-emitting layer 235 , second electron functional layer 236 . DETAILED DESCRIPTION
[0026] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application. In the present application, unless otherwise specified, the directional words such as "upper" and "lower" used are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is only for convenience and simplicity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values within the range. For example, description of a range from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the stated range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited numeral (fractional or integral) within the stated range.
[0027] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0028] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0029] In the present application, the single bond to which the substituent is connected runs through the corresponding ring, indicating that the substituent can be connected to any position of the ring. R1 can be connected to any substitutable position in the ring.
[0030] In the present application, when the same substituent appears multiple times, it can be independently selected from different groups. For example, if the above general formula may contain n R1s, each R1 can be independently selected from different groups.
[0031] The present application provides a method for preparing a thin film. Figure 1 , Figure 1 This is a flow chart of an embodiment of a method for preparing a thin film provided in the present application. The method specifically comprises the following steps:
[0032] Step S11: providing a composite material, wherein the composite material comprises an organic compound and an inorganic nanomaterial, wherein the inorganic nanomaterial comprises a metal oxide and a doped metal ion;
[0033] Step S12: placing the composite material on a substrate and subjecting it to light treatment to obtain a thin film.
[0034] Wherein, the structure of the organic compound is as shown in formula (I):
[0035]
[0036] wherein each R1 is independently selected from hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, a C1-C20 chain hydrocarbon group, a C1-C20 chain hydrocarbon oxy group, a cyclic hydrocarbon group having 3 to 60 ring atoms, a heterocyclic hydrocarbon group having 3 to 60 ring atoms, an aryl group having 5 to 60 ring atoms, a heteroaryl group having 5 to 60 ring atoms, an aryloxy group having 5 to 60 ring atoms, and a heteroaryloxy group having 5 to 60 ring atoms, which are unsubstituted or substituted with amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, or cyano, or a combination of one or more thereof; two adjacent R1s may form a ring or may not form a ring; and n is selected from any integer from 0 to 4;
[0037] R2 is selected from one of -C(R3)3, -N(R4)2, and -OR5;
[0038] wherein R3 is independently selected from hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, a C1-C20 chain hydrocarbon group, a C1-C20 chain hydrocarbon oxy group, a cyclic hydrocarbon group having 3 to 60 ring atoms, a heterocyclic hydrocarbon group having 3 to 60 ring atoms, an aryl group having 5 to 60 ring atoms, a heteroaryl group having 5 to 60 ring atoms, an aryloxy group having 5 to 60 ring atoms, and a heteroaryloxy group having 5 to 60 ring atoms, which is unsubstituted or substituted with amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, or cyano;
[0039] R4 is independently selected from hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, thiol, cyano, a combination of one or more of unsubstituted or amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, thiol, cyano, C1-C10 alkoxycarbonyl, C1-C10 chain hydrocarbon group, C3-C10 cycloalkyl substituted C1-C20 chain hydrocarbon group, C1-C20 chain hydrocarbon group, cycloalkyl group with 3 to 60 ring atoms, heterocycloalkyl group with 3 to 60 ring atoms, aryl group with 5 to 60 ring atoms, heteroaryl group with 5 to 60 ring atoms, aryloxy group with 5 to 60 ring atoms, heteroaryloxy group with 5 to 60 ring atoms, and two adjacent R4s may form a ring or not;
[0040] R5 is independently selected from hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, a combination of one or more of C1-C20 chain hydrocarbon groups, C1-C20 chain hydrocarbonoxy groups, cyclic hydrocarbon groups having 3 to 60 ring atoms, heterocyclic hydrocarbon groups having 3 to 60 ring atoms, aryl groups having 5 to 60 ring atoms, heteroaryl groups having 5 to 60 ring atoms, aryloxy groups having 5 to 60 ring atoms, and heteroaryloxy groups having 5 to 60 ring atoms, which are unsubstituted or substituted with one or more of amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1-C20 alkyl, -(C=O)-R7, and R7 is selected from one or more of C1-C20 alkyl groups, aromatic ring groups having 6 to 40 ring atoms, and aromatic heterocyclic groups having 5 to 40 ring atoms.
[0041] In this embodiment, in the inorganic nanomaterial doped with metal ions, the doped metal ions can be enriched on the surface of the inorganic nanomaterial, that is, the doped metal ions can be enriched on the surface of the metal oxide, and after the composite material including the inorganic nanomaterial doped with metal ions and the organic compound is set on the substrate, under light treatment, the organic compound itself undergoes ring formation to form a coumarin compound (structure such as formula (II)) and a semi-radical R2, wherein the semi-radical R2 combines with the doped metal ions on the surface of the inorganic nanomaterial, thereby reducing the solubility of the film in polar solvents and improving the anti-solvent and anti-solvent scouring properties of the film. For details, see Figure 2 , Figure 2 A schematic diagram of the connection between a semi-free radical R2 and the surface of the inorganic nanomaterial in a method for preparing a thin film is provided for the present application.
[0042]
[0043] In the present application, hydrocarbon groups include saturated hydrocarbon groups (such as alkyl groups) and unsaturated hydrocarbon groups (such as olefins and alkynes). Hydrocarbon groups are divided into chain hydrocarbon groups (such as straight-chain hydrocarbon groups or hydrocarbon groups containing straight chains) and cyclic hydrocarbon groups (such as cycloalkyl groups, cycloalkenyl groups, cycloalkynyl groups, etc.). Hydrocarbyloxy groups are groups of "-O-hydrocarbon groups", i.e., hydrocarbon groups are connected to other groups via oxygen atoms.
[0044] Furthermore, each R1 can be independently selected from one or more of halogen, hydroxyl, nitro, C1-10 alkyl, C1-10 alkoxy, C1-10 alkyl unsubstituted or substituted by one or more of halogen atoms, hydroxyl, amine, C1-10 alkyl, C1-10 alkoxy, aryl having 5-30 ring atoms, and aromatic heteroyl having 5-30 ring atoms, and two adjacent R1s may form a ring or not.
[0045] In one embodiment, each R1 can be independently selected from a halogen atom, a nitro group, or a C1-10 alkyl group, and two adjacent R1s may form a ring or not.
[0046] The C1-10 alkyl group may include one or more of methyl, ethyl, propyl, isopropyl, n-butyl, n-pentyl, cyclopentyl, n-hexyl, cyclohexyl, n-heptyl, n-octyl, n-nonyl, n-decyl and the like.
[0047] The halogen atoms include one or more of F, Cl, Br and I.
[0048] Wherein, n can be any integer selected from 0, 1, 2, 3, and 4. In one embodiment, n is selected from 0, 1 or 2.
[0049] In one specific embodiment, n is selected from 1, and R1 is selected from a halogen atom, a nitro group, and a C1-10 alkyl group.
[0050] In another specific embodiment, n is selected from 2, 3 or 4, wherein two adjacent R1s form a ring. Further, two adjacent R1s form a five-membered ring. It is understood that two adjacent R1s form a ring or do not form a ring, which means that two R1s can be connected to form a ring, specifically a three-membered ring, a four-membered ring, a five-membered ring, a six-membered ring, etc.
[0051] In one embodiment, R2 is selected from -C(R3)3.
[0052] In one embodiment, R3 is independently selected from hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, a C1-C20 chain hydrocarbon group which is unsubstituted or substituted with amino, halogen, hydroxyl, carboxyl, or nitro, a C1-C20 chain hydrocarbon oxy group, a cycloalkyl group having 3 to 60 ring atoms, a heterocycloalkyl group having 3 to 60 ring atoms, an aryl group having 5 to 60 ring atoms, a heteroaryl group having 5 to 60 ring atoms, an aryloxy group having 5 to 60 ring atoms, and a heteroaryloxy group having 5 to 60 ring atoms.
[0053] Furthermore, R3 is independently selected from one or more of H, deuterium, and C1-20 alkyl.
[0054] In one embodiment, R2 is selected from -N(R4)2.
[0055] In one embodiment, R4 is independently selected from one or more of hydrogen, deuterium, unsubstituted or substituted by one or more of halogen, hydroxyl, amine, C1-10 alkyl, -O(C=O)-R6, aryl with 6-18 ring atoms, heteroaryl with 5-18 ring atoms, and two adjacent R4s may form a ring or not, wherein R6 is selected from C1-10 alkyl.
[0056] In one embodiment, two adjacent R4s form a ring, and -N(R4)2 is selected from -OCOR6 substituted or unsubstituted Further, R6 is selected from C1-10 alkyl.
[0057] In one embodiment, R2 is selected from -OR5.
[0058] Furthermore, R5 is independently selected from one or more of H, a deuterium atom, a substituted or unsubstituted C1-10 alkyl group, a substituted or unsubstituted C1-10 alkenyl group, a substituted or unsubstituted C1-10 alkynyl group, a substituted or unsubstituted aromatic ring group having 6-18 ring atoms, and a substituted or unsubstituted aromatic heterocyclic group having 5-18 ring atoms, wherein the substituted substituent is selected from one or more of a halogen atom, a hydroxyl group, an amino group, a C1-10 alkyl group, and -(C=O)-R7, and R7 is selected from one or more of a C1-10 alkyl group, an aromatic ring group having 6-18 ring atoms, and an aromatic heterocyclic group having 5-18 ring atoms.
[0059] Furthermore, R5 is independently selected from one or more of hydrogen, deuterium, unsubstituted or substituted by one or more of halogen, hydroxyl, amino, C1-10 alkyl, -(C=O)-R7, C1-10 alkenyl, C1-10 alkynyl, aryl having 6-18 ring atoms, and heteroaryl having 5-18 ring atoms, wherein R7 is selected from one or more of C1-10 alkyl, aryl having 6-18 ring atoms, and heteroaryl having 5-18 ring atoms.
[0060] Further, R5 is independently selected from hydrogen, deuterium, C1-10 alkyl, C1-10 alkenyl, phenyl, naphthyl, biphenyl, or phenyl, naphthyl, biphenyl substituted by one or more of halogen, hydroxyl, amino, C1-10 alkyl, -(C=O)-R7, wherein R7 is selected from one or more of C1-10 alkyl, phenyl, biphenyl, naphthyl.
[0061] In one embodiment, the organic compound is selected from one or more of the following structures:
[0062]
[0063] Among them, -C8H 17 It is n-octyl.
[0064] In step S11:
[0065] In one embodiment, the mass ratio of the organic compound to the inorganic nanomaterial is 0.2-0.5:1, specifically 0.2-0.45:1, 0.25-0.45:1, 0.25-0.40:1, 0.30-0.40:1, 0.30-0.35:1, etc.
[0066] In one embodiment, the inorganic nanomaterial is selected from doped or undoped metal oxides, the undoped metal oxides include one or more of ZnO, TiO2, SnO2, NiO, W2O3, Mo2O3, ZrO2, Ta2O3, Ga2O3, SiO2, Al2O3, CaO, and HfO2, the doped metal oxides include the undoped metal oxides and doping elements, the doping elements include metal doping elements and non-metal doping elements, the metal doping elements include one or more of Mg, Ca, Li, Ga, Al, K, Co, Mn, Zr, W, Ti, La, Y, Gd, In, and Ce, and the non-metal doping elements include one or more of carbon elements and halogens. Specifically, the carbon element may be graphene, C60, etc. The halogens include one or more of F, Cl, Br, and I.
[0067] Specifically, when the doping element includes a metal doping element, the molar ratio of the metal doping element to the metal oxide is 0.05-0.1:1, and specifically can be 0.05-0.09:1, 0.06-0.09:1, 0.06-0.08:1, 0.07-0.08:1, 0.05-0.06:1, 0.09-0.1:1, etc.
[0068] When the doping element includes a non-metallic doping element, the molar ratio of the non-metallic doping element to the metal oxide is 0.05-0.1:1, specifically 0.05-0.09:1, 0.06-0.09:1, 0.06-0.08:1, 0.07-0.08:1, 0.05-0.06:1, 0.09-0.1:1, etc.
[0069] It is understandable that the type of the metal doping element is different from the type of the metal element in the metal oxide.
[0070] In one embodiment, the inorganic nanomaterial is selected from one or more of doped or undoped ZnO, TiO2, SnO2. In a specific embodiment, the inorganic nanomaterial is selected from doped or undoped ZnO.
[0071] In one embodiment, the metal doping element may be doped in the form of doped metal ions. Furthermore, the valence state of the doped metal ions is different from the valence state of the metal element in the metal oxide. For example, when the metal oxide is ZnO, the valence state of the doped metal ions is different from that of ZnO. 2+ The valence state of is different, not positive divalent, but can be +1, +3, +4, etc. For example, the doped metal ion can be La 3+ , Y 3+ , Gd 3+ 、In 3+ 、Ce 4+ One or more of .
[0072] Furthermore, the ionic radius of the doped metal ions is greater than the ionic radius of the metal ions in the metal oxide. Specifically, the ratio of the ionic radius of the doped metal ions to the ionic radius of the metal ions in the metal oxide is 130-200:100, and can be 130-180:100, 150-180:100, 130-150:100, 180-200:100, etc.
[0073] In this embodiment, the unequal doped metal ions will bring a large number of free electrons or holes in the inorganic nanomaterial, and these generated free electrons or holes will tend to be enriched on the surface of the inorganic nanomaterial to neutralize the surface charge, thereby promoting the enrichment of the doped metal ions on the surface of the nanometal oxide, thereby greatly reducing the surface defects of the inorganic nanomaterial.
[0074] Further, the lattice distortion caused by the doping metal ions with ionic radius in the above range entering the crystal structure of the metal oxide will become extremely severe due to the large ionic radius difference. The serious kinetic instability caused by this will prompt the doping metal ions to be enriched on the surface of the metal oxide, occupying the defect sites mainly composed of metal vacancies in the metal oxide, rather than entering the interior of the crystal structure to replace the metal sites of the metal oxide, thereby ensuring the metallographic structure of the metal oxide in the inorganic nano material, thereby ensuring the uniformity of material performance. That is, the doping metal ions can passivate defects and enable the inorganic nano material to maintain its inherent characteristics.
[0075] Further, in one embodiment, the molar percentage of the doped metal ions in all metal elements in the inorganic nanomaterial is 0.05-10%, specifically 0.1-10%, 0.1-8%, 0.5-8%, 0.5-6%, 1-6%, 1-4%, 2-4%, etc. The molar ratio of the doped metal ions can passivate the defects of the inorganic nanomaterial and make it have better crystal structure stability.
[0076] The metal cation ligand is connected to the surface of the inorganic nanomaterial. It is understandable that the inorganic nanomaterial can be prepared by a known method for preparing nanomaterials. For example, it can be prepared by a sol-gel method, a hydrothermal method, a low-temperature alcohol phase method, etc. This is not limited here.
[0077] In a specific embodiment, the inorganic nanomaterial is ZnO doped with metal ions, and the preparation method includes: providing a mixed solution of zinc salt, a metal salt doped with metal ions, and an alkali, and reacting to obtain zinc oxide nanoparticles doped with metal ions.
[0078] The zinc salt may include one or more of diethyl zinc and its hydrate, zinc oleate and its hydrate, zinc stearate and its hydrate, zinc acetate and its hydrate, zinc laurate and its hydrate, etc. The doped metal ions in the metal salt containing doped metal ions may include La 3+ , Y 3+ , Gd 3+ 、In 3+ 、Ce 4+ One or more of the above, wherein the anion in the metal salt containing the doped metal ion is a non-coordinating anion, which may include nitrate NO 3- , Fluoroborate BF 4- or OTf trifluoride - The base may include one or more of lithium hydroxide, sodium hydroxide, triethylamine, ethanolamine, etc. The solvent in the mixed solution may be selected according to the reaction conditions and the solubility of each solute. For example, it may include at least one of dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), an alcohol solvent with 2 to 8 carbon atoms, and an ether solvent with 2 to 8 carbon atoms. Further, the reaction of the mixed solution may be carried out at room temperature of 20 to 30°C.
[0079] In step S12:
[0080] In one embodiment, disposing the composite material on a substrate comprises: disposing a first mixture on the substrate, wherein the first mixture comprises the composite material and a solvent.
[0081] The solvent may include one or more of an alcohol solvent, an ether solvent, tetrahydrofuran, acetone, chlorobenzene, toluene, etc. Specifically, the alcohol solvent includes one or more of methanol, ethanol, ethylene glycol, isopropanol, n-butanol, etc. The ether solvent includes one or more of methyl ether, ethyl ether, etc.
[0082] In one embodiment, the concentration of the composite material is 20-30 mg / mL, specifically 20-28 mg / mL, 23-28 mg / mL, 23-25 mg / mL, 20-23 mg / mL, etc.
[0083] Specifically, the composite material is disposed on the substrate, which can be achieved by a solution method, wherein the solution method includes but is not limited to spin coating, coating, inkjet printing, scraping, dip pulling, immersion, spraying, rolling or casting.
[0084] Specifically, the wavelength range of the light treatment is 250-400nm, and specifically can be 250-385nm, 255nm-375nm, 255nm-365nm, 275nm-355nm, 275nm-350nm, 280nm-340nm, 300nm-320nm, etc. The light in the wavelength range is ultraviolet light, and the ultraviolet light is set to the substrate
[0085] The energy density of the light treatment can be 45 to 110 mJ / cm 2 , specifically 45 to 100 mJ / cm 2 , 50~100mJ / cm 2 , 50~80mJ / cm 2 、60~80mJ / cm 2 wait.
[0086] The light treatment time may be 30 to 60 seconds, specifically 30 to 50 seconds, 40 to 50 seconds, 30 to 40 seconds, 50 to 60 seconds, etc.
[0087] In one embodiment, after the light treatment, an initial thin film is obtained, and the initial thin film is cleaned to obtain the thin film.
[0088] Wherein, the cleaning includes: using a cleaning solvent to clean the initial film to remove substances that are not combined with the inorganic nanomaterial, such as generated coumarin compounds.
[0089] Specifically, the cleaning solvent includes one or more of alcohol solvents, ether solvents, tetrahydrofuran, acetone, chloroform, chlorobenzene, o-dichlorobenzene, toluene, etc. The alcohol solvent includes one or more of methanol, ethanol, ethylene glycol, isopropanol, n-butanol, etc. The ether solvent includes one or more of methyl ether, ethyl ether, etc.
[0090] Specifically, the cleaning solvent may be used to soak and clean the initial thin film, and the soaking and cleaning time is 30 to 60 seconds, specifically 30 to 50 seconds, 40 to 50 seconds, 30 to 40 seconds, 50 to 60 seconds, etc. For example, the substrate including the initial thin film is immersed in the cleaning solvent for soaking and cleaning.
[0091] After the cleaning, a drying process is further included, and the drying process can be vacuum drying or heat drying to remove the first solvent in the oxide particle solution as much as possible. The vacuum drying pressure can be 0.01-10 Pa, and the time can be 5-30 min. The heat drying temperature can be 40-150° C., and the time can be 5-60 min.
[0092] Specifically, the pressure of the vacuum drying can be 0.01-0.1Pa, 0.1-1Pa, 1-5Pa, 5-10Pa, etc., and the time can be 5-10min, 10-20min, 20-30min, etc. Specifically, the temperature of the heating drying can be 40-12°C, 60-120°C, 60-100°C, 80-100°C, 100-150°C, etc., and the time can be 5-10min, 10-20min, 20-30min, 30-40min, 40-50min, 50-60min, etc.
[0093] The drying process in the present application may be an annealing process. "Annealing process" includes all treatment processes that can make the wet film obtain higher energy, thereby changing from a wet film state to a dry state. For example, "annealing process" may only refer to a heat treatment process, that is, heating the wet film to a specific temperature, and then maintaining it for a specific time to allow the solvent in the wet film to fully evaporate; for example, "annealing process" may also include a heat treatment process and a cooling process performed in sequence, that is, heating the wet film to a specific temperature, and then maintaining it for a specific time to allow the solvent in the first wet film to fully evaporate, and then cooling it at an appropriate speed to eliminate residual stress and reduce the risk of layer deformation and cracking of the dried hole transport film.
[0094] The present application provides a film, which is prepared by the film preparation method provided by the present application.
[0095] See also Figure 3 , Figure 3The schematic diagram of the structure of an embodiment of a photoelectric device provided by the present application. The photoelectric device 100 provided by the present application includes a first electrode 10, a second electrode 20, and a functional layer 30, wherein the first electrode 10 and the second electrode 20 are arranged opposite to each other, and the functional layer 30 is arranged between the first electrode 10 and the second electrode 20, wherein the functional layer 30 includes the above-mentioned thin film or includes a thin film prepared by the above-mentioned thin film preparation method.
[0096] The first electrode 10 and the second electrode 20 form a pair of electrodes, one of which is a cathode and the other is an anode.
[0097] In this embodiment, the functional layer 30 of the optoelectronic device 100 includes a thin film prepared by the thin film preparation method provided in the present application. Since it has good solubility resistance, it can avoid structural damage and performance degradation caused by damage to the thin film, thereby improving the performance of the optoelectronic device.
[0098] In one embodiment, the functional layer 30 includes an electronic functional layer 31 , and the electronic functional layer 31 includes the above-mentioned thin film or includes a thin film prepared by the above-mentioned thin film preparation method.
[0099] In this embodiment, the electronic functional layer 31 includes a thin film prepared by the preparation method of the present application, and the thin film has good resistance to solvent erosion, thereby improving the film flatness of the electronic functional layer 31, improving the interface contact between the electronic functional layer 31 and the second electrode 20, and improving the interface contact between the electronic functional layer 31 and the light-emitting layer 32, and reducing the surface defects of the inorganic nanomaterials, thereby reducing the quenching of excitons, improving luminescence performance such as luminescence efficiency, and also improving the life and stability of the optoelectronic device 100.
[0100] The thickness of the electronic functional layer 31 is 20-60 nm, and specifically can be 20-50 nm, 30-50 nm, 30-40 nm, etc.
[0101] Furthermore, in one embodiment, the functional layer 30 further includes a light-emitting layer 32 , and the light-emitting layer 32 is disposed between the electronic functional layer 31 and the anode.
[0102] In one embodiment, the electronic functional layer 31 includes a first electron transport layer 311 and a second electron transport layer 312 , wherein the first electron transport layer 311 is disposed close to the cathode, and the second electron transport layer 312 is disposed close to the light emitting layer 32 .
[0103] In one embodiment, the inorganic nanomaterial in the first electron transport layer 311 further includes a first dopant, and the first dopant includes one or more of Ga, Li, Mg, Mn and halogen. The first electron transport layer 311 has a relatively small work function and can promote electron injection.
[0104] In one embodiment, the thickness of the first electron transport layer 311 may be 20-30 nm, specifically 20-28 nm, 23-28 nm, 23-25 nm, etc.
[0105] In one embodiment, the inorganic nanomaterial in the second electron transport layer 312 further includes a second dopant, and the second dopant includes one or more of Al, K, graphene, C60, MoS2, and a highly conductive polymer. The highly conductive polymer includes one or more of polyacetylene, polypyrrole, polyindole, and polyaniline.
[0106] The thickness of the second electron transport layer 312 may be 20-30 nm, specifically 20-28 nm, 23-28 nm, 23-25 nm, etc.
[0107] In one embodiment, the material of the light-emitting layer 32 is selected from organic light-emitting materials or quantum dot light-emitting materials;
[0108] The organic light-emitting material is selected from at least one of diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives or fluorene derivatives, TBPe fluorescent materials emitting blue light, TTPA fluorescent materials emitting green light, TBRb fluorescent materials emitting orange light, and DBP fluorescent materials emitting red light;
[0109] The quantum dot luminescent material is selected from at least one of single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials, the single structure quantum dots are selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds, the II-VI compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZ At least one of CdZnS, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbT e, SnPbSSe, SnPbSeTe, SnPbSTe, and the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, Ga At least one of InNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2; the core of the core-shell structured quantum dots is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the core-shell structured quantum dots is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS.
[0110] The perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl-, Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of .
[0111] When n = 2, the inorganic metal halide octahedron MX6 4- The metal cation M is located at the center of the halogen octahedron, and the organic amine cation B fills the gap between the octahedrons to form an infinitely extended three-dimensional structure. When n>2, the inorganic metal halide octahedron MX6 connected by the top-sharing method 4- It extends in two dimensions to form a layered structure, with an organic amine cation bilayer (protonated monoamine) or an organic amine cation monolayer (protonated diamine) inserted between the layers, and the organic layer and the inorganic layer overlap to form a stable two-dimensional layered structure.
[0112] In one embodiment, the quantum dots may be one or more of red quantum dots, green quantum dots, and blue quantum dots.
[0113] It is understandable that the surface of the quantum dots may be connected with ligands, which may include mercaptoacetic acid, mercaptopropionic acid, mercaptobutyric acid, mercaptooleic acid, etc. After the above ligands are coordinated with the surface atoms of the quantum dots, carboxylic acid groups will be modified on the surface of the quantum dots, which is conducive to improving the film-forming quality of the quantum dots, thereby improving the luminescence performance and stability of the optoelectronic device 100.
[0114] In one embodiment, the quantum dots may include: one or more of silicon quantum dots, germanium quantum dots, cadmium sulfide quantum dots, cadmium selenide quantum dots, cadmium telluride quantum dots, zinc selenide quantum dots, lead sulfide quantum dots, lead selenide quantum dots, indium phosphide quantum dots, indium arsenide quantum dots and gallium nitride quantum dots.
[0115] In one embodiment, the thickness of the light emitting layer 32 may be 20-50 nm, specifically 20-45 nm, 25-45 nm, 25-40 nm, 30-40 nm, 30-35 nm, etc.
[0116] In one embodiment, the functional layer 30 includes a hole functional layer 33, and the hole functional layer 33 is disposed between the light emitting layer 32 and the anode. Further, the hole functional layer 33 may include one or more layers of a hole transport layer 331 and a hole injection layer 332.
[0117] Specifically, the material of the hole transport layer 311 can be selected from organic materials with hole transport capability, including but not limited to poly(9,9-dioctylfluorene-co-N-(4-butylphenyl)diphenylamine) (TFB), polyvinylcarbazole (PVK), poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine) (poly-TPD), poly(9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylenediamine) (PFB), 4,4',4"-tri(carbazole-9-yl)triphenylamine (TCATA), 4,4'-bis(9-carbazole)biphenyl (CBP), N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'- One or more of diamine (TPD), N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (NPB), poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid) (PEDOT:PSS), 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline] (TAPC). The material of the hole transport layer 311 can also be selected from inorganic materials with hole transport capability, including but not limited to doped graphene, undoped graphene, C60, doped or undoped NiO, V2O5, CrO3, CuO, CuS, MoO3, MoS2, MoSe2, WO3, WS2, WSe2 and CuSCN.
[0118] In one embodiment, the thickness of the hole transport layer 311 may be 20-100 nm, specifically 20-80 nm, 40-80 nm, 40-60 nm, 50-60 nm, etc.
[0119] Specifically, the material of the hole injection layer 312 can be selected from materials with hole injection capability, including but not limited to PEDOT:PSS, CuPc (copper phthalocyanine), TiOPc (titanium phthalocyanine), m-MTDATA (CAS: 124729-98-2), 2-TNATA (4,4',4"-tris(2-naphthylphenylaminotriphenylamine), CAS: 185690-41-9), F4-TCNQ (CAS: 29261-33-4), HATCN (CAS: 105598-27-4), One or more of doped or undoped NiO, V2O5, CrO3, CuO, CuS, MoO3, MoS2, MoSe2, WO3, WS2, WSe2 and CuSCN. PEDOT:PSS is a high molecular polymer, and its Chinese name is poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonic acid). In one embodiment, the thickness of the hole injection layer 312 can be 20 to 50 nm, specifically 20 to 45 nm, 25 to 45 nm, 25 to 40 nm, 30 to 40 nm, 35 to 40 nm, etc.
[0120] The materials of the first electrode 10 and the second electrode 20 may be materials known in the art for cathodes, and the materials of the anode may be materials known in the art for anodes. The materials of the cathode and the anode are independently selected from one or more of a metal electrode, a carbon silicon electrode, a doped or undoped metal oxide electrode and a composite electrode; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca and Mg; the material of the carbon silicon electrode is selected from at least one of silicon, graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from at least one of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2. Wherein, " / " represents a stacked structure, for example, the composite electrode AZO / Ag / AZO represents an electrode of a composite structure of three layers stacked together consisting of an AZO layer, an Ag layer and an AZO layer. Specifically, the thickness of the first electrode 10 can be 10 to 1000 nm, specifically 10 to 800 nm, 100 to 800 nm, 100 to 600 nm, 200 to 600 nm, 200 to 400 nm, etc. The thickness of the second electrode 20 can be 10 to 1000 nm, specifically 10 to 800 nm, 100 to 800 nm, 100 to 600 nm, 200 to 600 nm, 200 to 400 nm, etc.
[0121] In a specific embodiment, the photoelectric device 100 includes a first electrode 10, a second electrode 20, a light-emitting layer 32, an electronic functional layer 31, and a hole functional layer 33, wherein the light-emitting layer 32 is arranged between the first electrode 10 and the second electrode 20, the electronic functional layer 31 is arranged between the light-emitting layer 32 and the second electrode 20, and the hole functional layer 33 is arranged between the light-emitting layer 32 and the first electrode 10.
[0122] Furthermore, in a specific embodiment, the hole functional layer 33 includes two layers, a hole transport layer 311 and a hole injection layer 312 . The hole transport layer 311 is arranged close to the light emitting layer 32 , and the hole injection layer 312 is arranged close to the first electrode 10 .
[0123] In one embodiment, the electronic functional layer 31 also includes an electron injection layer (not shown), which is arranged close to the second electrode 20. The material of the electron injection layer is a material known in the art for electron injection layers, for example, it can be selected from but not limited to at least one of LiF, LiF / Yb, MgP, MgF2, Al2O3, Ga2O3, ZnO, Cs2CO3, Rb2CO3, and RbBr.
[0124] It is understood that, in addition to the above-mentioned functional layers, the optoelectronic device 100 may also be provided with some functional layers conventionally used in optoelectronic devices that help improve the performance of the optoelectronic device, such as an electron blocking layer, a hole blocking layer, an interface modification layer, etc. It is understood that the material and thickness of each layer of the optoelectronic device 100 may be adjusted according to the light emission requirements of the optoelectronic device 100.
[0125] It can be understood that the material and thickness of each layer of the optoelectronic device 100 can be set and adjusted accordingly according to the performance requirements of the optoelectronic device 100, such as light emission requirements.
[0126] The optoelectronic device 100 further includes a substrate (not shown), which may also be referred to as a substrate. The substrate may be a rigid substrate or a flexible substrate. The rigid substrate may be a ceramic material or various glass materials. The flexible substrate may be a substrate formed of materials such as polyimide film (PI) and its derivatives, polyethylene naphthalate (PEN), phosphoenolpyruvic acid (PEP) or diphenylene ether resin. In one embodiment, the material of the substrate includes glass, silicon wafer, polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyether sulfone, or a combination thereof.
[0127] It can be understood that the photoelectric device 100 can be an upright or inverted photoelectric device. When the photoelectric device 100 is an upright photoelectric device, the substrate is combined with the side of the anode away from the light-emitting layer 32. When the photoelectric device 100 is an inverted photoelectric device, the substrate is combined with the side of the cathode away from the light-emitting layer 32.
[0128] It should be noted that the first electrode 10, the second electrode 20, the light-emitting layer 32 and other functional layers in the present application can be prepared by conventional techniques in the art, including but not limited to solution method and deposition method, wherein the solution method includes but is not limited to spin coating, coating, inkjet printing, scraping, dip pulling, immersion, spraying, rolling or casting; the deposition method includes chemical method and physical method, the chemical method includes but is not limited to chemical vapor deposition, continuous ion layer adsorption and reaction method, anodization method, electrolytic deposition method or coprecipitation method, and the physical method includes but is not limited to thermal evaporation coating method, electron beam evaporation coating method, magnetron sputtering method, multi-arc ion plating method, physical vapor deposition method, atomic layer deposition method or pulsed laser deposition method. When the first electrode 10, the second electrode 20, the light-emitting layer 32 and other functional layers are prepared by the solution method, a drying process needs to be added.
[0129] In one embodiment, see Figure 4 , Figure 4 A schematic diagram of the structure of another embodiment of a photoelectric device provided in the present application. The photoelectric device 200 is a stacked device, including a first electrode 210, a functional layer 230 and a second electrode 220, wherein the first electrode 210 and the second electrode 220 are arranged opposite to each other, the functional layer 230 is arranged between the first electrode 210 and the second electrode 220, and the functional layer 230 includes a first hole functional layer 231, a first light-emitting layer 232, a first electron functional layer 233, a second hole functional layer 234, a second light-emitting layer 235, and a second electron functional layer 236 arranged in sequence.
[0130] The first electronic functional layer 233 and the second electronic functional layer 236 may refer to the related description of the electronic functional layer 31 in the previous embodiment, which will not be described in detail here.
[0131] The first light-emitting layer 232 and the second light-emitting layer 235 may refer to the relevant description of the light-emitting layer 32 in the previous embodiment, and will not be described in detail here.
[0132] In one embodiment, the first hole functional layer 231 may include one or two layers of a first hole injection layer (not shown) and a first hole transport layer (not shown), and the second hole functional layer 234 may include one or two layers of a second hole injection layer (not shown) and a second hole transport layer (not shown). The first hole functional layer 231 and the second hole functional layer 234 may refer to the relevant description of the hole functional layer 33 in the previous embodiment, and will not be repeated here.
[0133] The first electrode 210 and the second electrode 220 are a pair of electrodes, one of which is an anode and the other is a cathode. Specifically, the first hole injection layer 231 in the functional layer 230 is arranged close to the anode, and the second electron transport layer 238 is arranged close to the cathode. Specifically, the first electrode 210 and the second electrode 220 can refer to the relevant description of the first electrode 10 and the second electrode 20 in the previous embodiment, and will not be repeated here.
[0134] It is understandable that the preparation method of the optoelectronic device may further include a packaging step. The packaging material may be acrylic resin or epoxy resin. The packaging may be machine packaging or manual packaging. UV curing glue sealing may be used. The concentrations of oxygen and water in the environment during the packaging step are both lower than 0.1ppm to ensure the stability of the optoelectronic device.
[0135] The embodiment of the present application also provides a display device, including the optoelectronic device provided by the present application. The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptop computers, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, wherein the smart wearable device can be, for example, a smart bracelet, a smart watch, a virtual reality (VR) helmet, etc.
[0136] The technical scheme and technical effects of the present application are described in detail below through specific embodiments, comparative examples and experimental examples. The following embodiments are only some embodiments of the present application and do not specifically limit the present application.
[0137] Example 1
[0138] Step 1: Provide a mixed solution of a composite material and ethanol, the concentration of the composite material is 25 mg / mL, and the composite material is composed of In 3+ The doped ZnO nanomaterial and the organic compound 1 (CAS: 86774-83-6, the structure is as follows), wherein the mass ratio of the organic compound to the ZnO nanomaterial is 0.5:1, In 3+ The total molar concentration of metal elements in ZnO nanomaterials is 10%.
[0139] Step 2: Spin the mixed solution onto the substrate and irradiate it with light using ultraviolet light with a wavelength of 255 nm and an energy density of 50 mJ / cm 2 , time is 10s; then the substrate after light treatment is immersed in ethanol solution for 10s for cleaning.
[0140] Step 3: The cleaned substrate is annealed at 100° C. for 10 minutes to obtain a thin film.
[0141]
[0142] Example 2
[0143] This embodiment is basically the same as embodiment 1, except that the doping metal ion in step 1 is La 3+ Instead of In 3+ .
[0144] Example 3
[0145] This embodiment is basically the same as Embodiment 1, except that the mass ratio of the organic compound to the ZnO nanomaterial in Step 1 is 0.2:1.
[0146] Example 4
[0147] This embodiment is basically the same as embodiment 1, except that: In step 1 3+ The total molar concentration of metal elements in ZnO nanomaterials is 0.1%.
[0148] Example 5
[0149] This embodiment is basically the same as embodiment 1, except that: In step 1 3+ The total molar concentration of metal elements in ZnO nanomaterials is 5%.
[0150] Example 6
[0151] This embodiment is basically the same as the embodiment 1, except that: in step 1, the organic compound 2 is used instead of the organic compound 1; in step 2, the wavelength of the light treatment is 365 nm, and the energy density of the light treatment is 50 mJ / cm 2 , time is 10s.
[0152]
[0153] Example 7
[0154] This embodiment is basically the same as the embodiment 1, except that: in step 1, the organic compound 3 is used instead of the organic compound 1; in step 2, the wavelength of the light treatment is 385 nm, and the energy density of the light treatment is 50 mJ / cm 2 , time is 10s.
[0155]
[0156] Example 8
[0157] This embodiment is basically the same as the embodiment 1, except that: in step 1, the organic compound 4 is used instead of the organic compound 1; in step 2, the wavelength of the light treatment is 350nm, and the energy density of the light treatment is 50mJ / cm 2 , time is 10s.
[0158]
[0159] Example 9
[0160] This embodiment is basically the same as the embodiment 1, except that: in step 1, the organic compound 5 is used instead of the organic compound 1; in step 2, the wavelength of the light treatment is 380nm, and the energy density of the light treatment is 50mJ / cm 2 , time is 10s.
[0161]
[0162] Example 10
[0163] This embodiment is basically the same as the embodiment 1, except that: in step 1, the organic compound 6 is used instead of the organic compound 1; in step 2, the wavelength of the light treatment is 380nm, and the energy density of the light treatment is 50mJ / cm 2 , time is 10s.
[0164]
[0165] Embodiment 11
[0166] This embodiment is basically the same as the embodiment 1, except that: in step 1, the organic compound 7 is used instead of the organic compound 1; in step 2, the wavelength of the light treatment is 375 nm, and the energy density of the light treatment is 50 mJ / cm 2 , time is 10s.
[0167]
[0168] Example 12
[0169] This embodiment is basically the same as the embodiment 1, except that: in step 1, the organic compound 8 is used instead of the organic compound 1; in step 2, the wavelength of the light treatment is 380nm, and the energy density of the light treatment is 50mJ / cm 2 , time is 10s.
[0170]
[0171] Embodiment 13
[0172] This embodiment is basically the same as the embodiment 1, except that the composite material is composed of ZnO nanomaterial and organic compound 1, and the ZnO nanomaterial is used instead of In 3+ Doped ZnO nanomaterials.
[0173] Comparative Example 1
[0174] Step 1: Provide an ethanol solution of ZnO nanomaterials, wherein the concentration of the ZnO nanomaterials is 25 mg / mL.
[0175] Step 2: Spin-coat the above solution onto a substrate and anneal at 100° C. for 10 min to obtain a thin film.
[0176] Comparative Example 2
[0177] Step 1: Provide In 3+ Ethanol solution of doped ZnO nanomaterials, In 3+ The molar concentration in the doped ZnO nanomaterial is 1%.
[0178] Step 2: Spin-coat the mixed solution onto a substrate and anneal at 100°C for 10 min to obtain a thin film.
[0179] test:
[0180] The thin films of Examples 1-13 and Comparative Examples 1-2 were spin-coated with an ethanol solvent, and then dried to remove the solvent. The surface roughness of the dried thin films was tested. The results are shown in Table 1.
[0181] Table 1
[0182] Group Surface roughness Ra(nm) Comparative Example 1 2.56 Comparative Example 2 2.01 Comparative Example 3 3.21 Example 1 1.75 Example 2 1.70 Example 3 1.75 Example 4 1.85 Example 5 1.83 Example 6 1.86 Example 7 1.73 Example 8 1.77 Example 9 1.80 Example 10 1.85 Embodiment 11 1.76 Example 12 1.82
[0183] It can be seen from Table 1 that compared with comparative examples 1-3, the surface roughness of the films of embodiments 1-12 after washing with ethanol solvent is relatively small, indicating that the preparation method of the film provided in the present application can improve the solubility of the film in polar solvents in the inorganic material, and improve the solubility and solution erosion resistance of the film.
[0184] Device Example 1
[0185] The device embodiment 1 provides an inverted quantum dot light emitting diode, and the preparation method of the quantum dot light emitting diode is as follows:
[0186] Step 1: On a 100 nm thick ITO layer, an electron transport layer with a thickness of 20 nm is prepared according to the thin film preparation method of Example 1;
[0187] Step 2: depositing a CdSe blue quantum dot solution on the electron transport layer to obtain a light-emitting layer, the thickness of the light-emitting layer being 30 nm;
[0188] Step 3: depositing a layer of PEDOT:PSS on the hole transport layer to obtain a hole injection layer with a thickness of 50 nm;
[0189] Step 4: Deposit Ag on the hole injection layer to obtain an anode with a thickness of 100 nm.
[0190] Device Examples 2-12
[0191] This device embodiment is basically the same as device embodiment 1, and the only difference is that in step 1, an electron transport layer with a thickness of 20 nm is prepared according to the thin film preparation method of embodiments 2-12 respectively.
[0192] Device Example 13
[0193] This device embodiment is basically the same as device embodiment 1, and the only difference is that: in step 1, a first electron transport layer with a thickness of 20 nm is prepared according to the thin film preparation method of embodiment 1, wherein the ZnO nanomaterial is Mg-doped ZnO (i.e., ZnMgO), and the molar ratio of Mg to ZnO is 1:10; then a second electron transport layer with a thickness of 20 nm is prepared according to the thin film preparation method of embodiment 1, wherein the ZnO nanomaterial is Al-doped ZnO (i.e., ZnO), and the molar ratio of Al to ZnO is 1:10.
[0194] Device Example 14
[0195] Step 1: Deposit 100nm of ITO on a glass substrate;
[0196] Step 2: Deposit a hole injection layer Pedot:PSS on ITO with a thickness of 50nm;
[0197] Step 3: deposit a hole transport layer PVK on the hole injection layer with a thickness of 20 nm;
[0198] Step 4: deposit a layer of cadmium selenide blue light-emitting quantum dots on the hole transport layer with a thickness of 30 nm;
[0199] Step 5: preparing an electron transport layer with a thickness of 20 nm according to the thin film preparation method of Example 1, wherein the ZnO nanomaterial is Mg-doped ZnO (ie, ZnMgO), and the molar ratio of Mg to ZnO is 1:10;
[0200] Step 6: Deposit a hole injection layer Pedot:PSS on the electron transport layer with a thickness of 50nm;
[0201] Step 7: deposit a hole transport layer PVK on the hole injection layer with a thickness of 20 nm;
[0202] Step 8: deposit a layer of cadmium selenide blue light-emitting quantum dots on the hole transport layer with a thickness of 30 nm;
[0203] Step 9: Deposit a layer of ZnMgO on the quantum dots with a thickness of 20 nm;
[0204] Step 10: Deposit 100nm thick Ag.
[0205] Device Comparison Examples 1-3
[0206] The device comparative example is basically the same as device embodiment 1, and the only difference is that in step 1, an electron transport layer with a thickness of 20 nm is prepared according to the thin film preparation method of comparative examples 1-3.
[0207] Device Comparison Example 4
[0208] The device comparative example is basically the same as device embodiment 13, and the only difference is that in step 1, ZnMgO is first deposited to obtain a first electron transport layer; and then ZnAlO is deposited to obtain a second electron transport layer.
[0209] Device Comparison Example 5
[0210] The device comparative example is basically the same as device embodiment 14, with the only difference being that ZnMgO is directly deposited in step 5 to obtain an electron transport layer.
[0211] test
[0212] The quantum dot light-emitting diodes in Examples 1-14 and Comparative Examples 1-5 were tested for performance and lifespan, and the test indicators included the maximum current efficiency CE-max, the external quantum efficiency EQE, the current density J, and the time T95@1Knite for the device to decay from 100% to 95% at an initial brightness of 1Knite. The test results are detailed in Table 2 below.
[0213] The detection method of quantum efficiency EQE is as follows: using FSD FPD optical property measurement equipment, through LabView to control the efficiency test system built by QE PRO spectrometer, Keithley 2400, and Keithley 6485, to measure the parameters such as start-up voltage, current, brightness, and luminescence spectrum, and calculate the maximum current efficiency CE-max, external quantum efficiency EQE, and current density J; T95@1Knite uses FSD FPD optical property measurement equipment, through Keithley 2400, CS-160 brightness meter, and photodiode detector to build a life system to test the measured life T95, and calculate T95@1Knite through the measured life T95.
[0214] Table 2
[0215]
[0216] It can be seen from Table 2 that compared with device comparison examples 1-3, the current efficiency CE-max, external quantum efficiency EQE, current density J and life T95@1Knite of embodiments 1-13 are all improved, indicating that the electron transport layer prepared by the thin film preparation method of the present application can improve the luminescence efficiency, luminescence stability and other luminescence performance and life of the optoelectronic device.
[0217] Compared with device comparison example 4, device example 13, which also includes two electron transport layers, has better current efficiency CE-max, external quantum efficiency EQE, current density J and lifetime T95@1Knite, indicating that the two electron transport layers prepared by the thin film preparation method provided in the present application can improve the luminescence efficiency, luminescence stability and other luminescence performance and lifetime of the stacked device.
[0218] Compared with device comparison example 5, device example 14, which is also a stacked device, has better current efficiency CE-max, external quantum efficiency EQE, current density J and lifetime T95@1Knite, indicating that the electron transport layer prepared by the thin film preparation method provided in the present application can improve the luminescence efficiency, luminescence stability and other luminescence properties and lifetime of the stacked device.
[0219] Specifically, the present application can improve the solubility resistance of the film and make the film have better electron transmission performance through the film preparation method, thereby improving the performance and life of the optoelectronic device containing the film.
[0220] The above is a detailed introduction to the thin film preparation method, optoelectronic device and display device provided in the embodiments of the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A method for preparing a thin film, characterized in that: include: A composite material is provided, the composite material comprising an organic compound and an inorganic nanomaterial, the inorganic nanomaterial comprising a metal oxide and a doped metal ion; placing the composite material on a substrate and subjecting it to light treatment to obtain the film; Wherein, the structure of the organic compound is shown in formula (I): Each R1 is independently selected from hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, unsubstituted or substituted with amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1-C20 chain hydrocarbon group, C1-C20 chain hydrocarbon oxy group, cycloalkyl group with 3 to 60 ring atoms, heterocycloalkyl group with 3 to 60 ring atoms, aryl group with 5 to 60 ring atoms, heteroaryl group with 5 to 60 ring atoms, aryloxy group with 5 to 60 ring atoms, heteroaryloxy group with 5 to 60 ring atoms, two adjacent R1s may form a ring or not, and n is selected from any integer from 0 to 4; R2 is selected from one of -C(R3)3, -N(R4)2, and -OR5; wherein R3 is independently selected from hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, a C1-C20 chain hydrocarbon group, a C1-C20 chain hydrocarbon oxy group, a cyclic hydrocarbon group having 3 to 60 ring atoms, a heterocyclic hydrocarbon group having 3 to 60 ring atoms, an aryl group having 5 to 60 ring atoms, a heteroaryl group having 5 to 60 ring atoms, an aryloxy group having 5 to 60 ring atoms, and a heteroaryloxy group having 5 to 60 ring atoms, which is unsubstituted or substituted with amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, or cyano; R4 is independently selected from hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, thiol, cyano, a combination of one or more of unsubstituted or amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, thiol, cyano, C1-C10 alkoxycarbonyl, C1-C10 chain hydrocarbon group, C3-C10 cycloalkyl substituted C1-C20 chain hydrocarbon group, C1-C20 chain hydrocarbon group, cycloalkyl group with 3 to 60 ring atoms, heterocycloalkyl group with 3 to 60 ring atoms, aryl group with 5 to 60 ring atoms, heteroaryl group with 5 to 60 ring atoms, aryloxy group with 5 to 60 ring atoms, heteroaryloxy group with 5 to 60 ring atoms, and two adjacent R4s may form a ring or not; R5 is independently selected from hydrogen, deuterium, amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, a combination of one or more of C1-C20 chain hydrocarbon groups, C1-C20 chain hydrocarbonoxy groups, cyclic hydrocarbon groups having 3 to 60 ring atoms, heterocyclic hydrocarbon groups having 3 to 60 ring atoms, aryl groups having 5 to 60 ring atoms, heteroaryl groups having 5 to 60 ring atoms, aryloxy groups having 5 to 60 ring atoms, and heteroaryloxy groups having 5 to 60 ring atoms, which are unsubstituted or substituted with one or more of amino, halogen, hydroxyl, carboxyl, nitro, sulfonic acid, aldehyde, mercapto, cyano, C1-C20 alkyl, -(C=O)-R7, and R7 is selected from one or more of C1-C20 alkyl groups, aromatic ring groups having 6 to 40 ring atoms, and aromatic heterocyclic groups having 5 to 40 ring atoms.
2. The preparation method according to claim 1, characterized in that: Each R1 is independently selected from one or more of hydrogen, halogen, hydroxyl, nitro, C1-C10 alkyl, C1-C10 alkoxy, C1-C10 alkyl unsubstituted or substituted by one or more of halogen atoms, hydroxyl, amine, C1-C10 alkyl, C1-C10 alkoxy, aryl having 5 to 30 ring atoms, and aromatic heteroyl having 5 to 30 ring atoms, and two adjacent R1s may form a ring or not; and / or R3 are each independently selected from one or more of hydrogen, deuterium, C1-20 alkyl; and / or R4 is independently selected from one or more of hydrogen, deuterium, unsubstituted or substituted by one or more of halogen, hydroxyl, amine, C1-C10 alkyl, -O(C=O)-R6, aryl with 6 to 18 ring atoms, heteroaryl with 5 to 18 ring atoms, and two adjacent R4s may form a ring or not, wherein R6 is selected from C1-C10 alkyl; and / or R5 is independently selected from one or more of hydrogen, deuterium, unsubstituted or substituted by one or more of halogen, hydroxyl, amine, C1-C10 alkyl, -(C=O)-R7, C1-C10 alkenyl, C1-C10 alkynyl, aryl having 6 to 18 ring atoms, and heteroaryl having 5 to 18 ring atoms, wherein R7 is selected from one or more of C1-C10 alkyl, aryl having 6 to 18 ring atoms, and heteroaryl having 5 to 18 ring atoms.
3. The preparation method according to claim 1, characterized in that: The organic compound is selected from one or more of the following structures:
4. The preparation method according to any one of claims 1 to 3, characterized in that The mass ratio of the organic compound to the inorganic nanomaterial is 0.2 to 0.5:1; and / or The metal oxide includes one or more of ZnO, TiO2, SnO2, NiO, W2O3, Mo2O3, ZrO2, Ta2O3, Ga2O3, SiO2, Al2O3, CaO, HfO2; and / or The metal element in the doped metal ion is selected from one or more of Mg, Ca, Li, Ga, Al, K, Co, Mn, Zr, W, Ti, La, Y, Gd, In, and Ce; and / or The doped metal ions are enriched on the surface of the metal oxide; and / or The valence state of the doped metal ions is different from the valence state of the metal ions in the metal oxide; and / or The ionic radius of the doped metal ions is larger than the ionic radius of the metal ions in the metal oxide; and / or The molar percentage of the doped metal ions to all metal elements in the inorganic nanomaterial is 0.05-10%.
5. The preparation method according to claim 4, characterized in that: The ratio of the ionic radius of the doped metal ions to the ionic radius of the metal ions in the metal oxide is 130-200:100; and / or The metal oxide includes ZnO, and the doped metal ions include La 3+ , Y 3+ , Gd 3+ 、In 3+ 、Ce 4+ One or more of; and / or The inorganic nanomaterial also includes other dopants, which include metal doping elements and non-metal doping elements. The metal doping elements include one or more of Mg, Ca, Li, Ga, Al, K, Co, Mn, Zr, W, Ti, La, Y, Gd, In, and Ce, and the non-metal doping elements include one or more of carbon elements and halogens.
6. The preparation method according to claim 1, characterized in that: The wavelength range of the light treatment is 250-400 nm; and / or The energy density of the light treatment is 45 to 110 mJ / cm 2 ; and / or The light treatment time is 30 to 60 seconds; and / or The step of arranging the composite material on the substrate comprises: arranging a composite material solution on the substrate, wherein the concentration of the composite material in the composite material solution is 20-30 mg / mL.
7. The preparation method according to claim 1, characterized in that: After the light treatment, the film is washed and dried to obtain the film; The solvent used for cleaning includes one or more of alcohol solvents, ether solvents, tetrahydrofuran, acetone, chloroform, chlorobenzene, o-dichlorobenzene, and toluene.
8. A photoelectric device, characterized in that: include: A first electrode and a second electrode arranged opposite to each other; A functional layer is arranged between the first electrode and the second electrode, wherein the functional layer comprises a thin film prepared by the method for preparing a thin film according to any one of claims 1 to 7.
9. The optoelectronic device according to claim 8, characterized in that: The functional layer includes a hole functional layer, a light emitting layer and the electron functional layer arranged in sequence; or, The functional layer includes a first hole functional layer, a first light-emitting layer, a first electron functional layer, a second hole functional layer, a second light-emitting layer and a second electron functional layer arranged in sequence, wherein the first electron functional layer and / or the second electron functional layer includes a thin film prepared by the method for preparing the thin film described in any one of items 1-7.
10. The optoelectronic device according to claim 9, characterized in that: The functional layer includes a first electron transport layer and a second electron transport layer, the first electron transport layer is arranged away from the light-emitting layer, and the second electron transport layer is arranged close to the light-emitting layer; Wherein, the inorganic nanomaterial in the first electron transport layer further includes a first dopant, and the first dopant includes one or more of Ga, Li, Mg, Mn and halogen; and / or, The inorganic nanomaterial in the second electron transport layer further includes a second dopant, and the second dopant includes one or more of Al, K, graphene, C60, MoS2, polyacetylene, polypyrrole, polyindole and polyaniline.
11. The optoelectronic device according to claim 9, characterized in that: The material of the light-emitting layer, the first light-emitting layer or the second light-emitting layer is selected from organic light-emitting materials or quantum dot light-emitting materials; the organic light-emitting material is selected from at least one of diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives or fluorene derivatives, TBPe fluorescent materials emitting blue light, TTPA fluorescent materials emitting green light, TBRb fluorescent materials emitting orange light and DBP fluorescent materials emitting red light; the quantum dot light-emitting material is selected from at least one of single-structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials, and the single-structure quantum dots are selected from II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds At least one of the II-VI Group compounds is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnS The IV-VI group compound is selected from at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, and the III-V group compound is selected from at least one of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNS b, at least one of GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compound is selected from at least one of CuInS2, CuInSe2 and AgInS2;The core of the quantum dots of the core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs; + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl-, Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - , at least one of I-; and / or, The hole functional layer, the first hole functional layer and the second hole functional layer independently include one or more layers of a hole transport layer and a hole injection layer, and the material of the hole transport layer includes poly(9,9-dioctylfluorene-co-N-(4-butylphenyl)diphenylamine), polyvinylcarbazole, poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine), poly(9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylenediamine), 4,4',4"-tri(carbazole-9-yl)triphenylamine, 4,4'-bis(9-carbazole)biphenyl, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'- diamine, poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonic acid), 4,4'-cyclohexylbis[N,N-bis(4-methylphenyl)aniline], doped or undoped graphene, C60, NiO, V2O5, CrO3, CuO, CuS, MoO3, MoS2, MoSe2, WO3, WS2, WSe2 and CuSCN, the material of the hole injection layer includes PEDOT:PSS, CuPc, TiOPc, m-MTDATA, 2-TNATA, F4-TCNQ, HATCN, doped or undoped NiO, V2O5, CrO3, CuO, CuS, MoO3, MoS2, MoSe2, WO3, WS2, WSe2 and CuSCN; and / or, The first electrode and the second electrode are independently selected from one or more of a metal electrode, a carbon silicon electrode, a doped or undoped metal oxide electrode and a composite electrode; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca and Mg; the material of the carbon silicon electrode is selected from at least one of silicon, graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from at least one of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2.
12. A display device, characterized in that: The display device comprises the optoelectronic device according to any one of claims 8 to 11.